Comparison of growth, basal area and survival rates in ten exotic and native species in Northern Sweden - Del Rey Morris, Kevin (2011)
As choice of species is important to reforest harvested areas and regenerate damaged areas, the present study compares growth of ten different species in Northern Sweden. Height growth, diameter, basal area and survival rates were compared, fifteen years after planting. By regression analysis, relationship between diameter and height was studied, suggesting that species which grew faster until that age were pioneer species as Betula pendula, Larix sukaczewii and Pinus contorta. Abies and Picea species showed the lowest values for all the parameter except for the survival rate. This agrees with its slow growth under the shade of pioneer species. Pinus species had the largest values for basal area; although this parameter doesn’t highlight the reality in the site due to many trees of slow growth species didn’t reach breast height and thus, these species had low basal areas. Pinus contorta, P. banksiana and Larix sukaczewii seem to be the exotic species best adapted to site conditions in the studied area, but further research will determine how the rest of the species can fit to the northern part of the country. The different characteristics of the species together with the location and desired final product will determine the choice of species.